Large-scale correlation analysis of deep venous thrombosis and gut microbiota - Yang, Mingyi; Luo, Pan; Zhang, Feng; Xu, Ke; Feng, Ruoyang; Xu, Peng (Frontiers in Cardiovascular Medicine, 2022)
Objective: Based on genome-wide association study summary data of a large population, the genetic correlation between the gut microbiota and deep venous thrombosis was analyzed. Methods: Linkage disequilibrium score regression has great potential in analyzing the heritability of disease traits or character traits. Linkage disequilibrium score regression was used to analyze the genetic correlation between the gut microbiota and deep venous thrombosis based on genome-wide association study summary data obtained from previous studies. Results: Streptococcaceae (rg = -0.5417, P value = 0.0221), Dialister (rg = -0.6225, P value = 0.0486), Streptococcus (rg = -0.5764, P value = 0.0288), and Lactobacillales (rg = -0.4839, P value = 0.0415) were found to have a significant genetic correlation with deep venous thrombosis. Conclusion: Our results not only help explain the mechanism of deep venous thrombosis but also provide a new direction for research into the prevention of deep venous thrombosis.